2015
DOI: 10.1002/crat.201500038
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ZnO films in different solvents and their photocatalytic activities

Abstract: ZnO thin films have been successfully synthesized via the chemical bath deposition (CBD) method without using any catalysts or templates. The effects of solvents (such as water, ethanol and n‐propanol) on structure and morphology of ZnO thin films have been studied. XRD analysis showed that all ZnO thin films with wurtzite crystal structure were obtained via various solvents. SEM images showed that ZnO thin films prepared in different solvents have different sizes and morphologies. TEM images showed that cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…26 Hence, increasing the polarity of the solvent will enhance growth in the (002) direction, due to strong interactions between the polar (002) surface and the polar solvent, which is likely to reduce the surface energy. 26,27 This trend was observed in the XRD patterns ( Fig. 1), and was quantied by determining the texture coefficients of the lms.…”
Section: Crystal Structurementioning
confidence: 69%
See 1 more Smart Citation
“…26 Hence, increasing the polarity of the solvent will enhance growth in the (002) direction, due to strong interactions between the polar (002) surface and the polar solvent, which is likely to reduce the surface energy. 26,27 This trend was observed in the XRD patterns ( Fig. 1), and was quantied by determining the texture coefficients of the lms.…”
Section: Crystal Structurementioning
confidence: 69%
“…Yang et al deposited ZnO thin films via the chemical bath deposition (CBD) method, using different solvents. 27 They observed an increase in preferred orientation in the (002) direction when more polar solvents were used. Tomakin et al observed the same phenomenon for their ZnO thin films deposited by spray pyrolysis.…”
Section: Resultsmentioning
confidence: 98%
“…In previously published results, ZnO crystallites with different morphologies can be observed by using different solvents, such as water, ethanol and n-propanol. 43 The surface tensions of these solvents are very different from each other, so the final composite morphology can be varied easily by changing the solvent.…”
Section: Tem Analysismentioning
confidence: 99%
“…For this purpose, this paper aimed to obtain pellets as the immobilization form using ZnO by slip casting. There are other papers in the literature that have obtained ZnO in other forms of immobilization, such as thin films [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%